Circulating levels of miR‐122 and nonalcoholic fatty liver disease in pre‐pubertal obese children. Issue 3 (22nd December 2017) - Brandt, S.; Roos, J.; Inzaghi, E.; Kotnik, P.; Kovac, J.; Battelino, T.; Cianfarani, S.; Nobili, V.; Colajacomo, M.; Kratzer, W.; Denzer, C.; Fischer‐Posovszky, P.; et al.
Summary: Objectives: The liver‐specific miR‐122 was proposed as biomarker for NAFLD in adults. Here, we investigated the relationship between miR‐122 levels, parameters of liver metabolism and NAFLD in pre‐pubertal obese children. Methods: Parameters of liver metabolism (ALT, AST and GGT) of three European cohorts were included (German cohort [ n = 71; age: 11.53 ± 1.29 years; BMI z‐score: 2.96 ± 0.64], Italian cohort [ n = 45; age: 9.60 ± 2.11 years; BMI z‐score: 3.57 ± 1.16], Slovenian cohort [ n = 31; age: 7.53 ± 1.47 years; BMI z‐score: 3.66 ± 0.88]). MiR‐122 levels and CK18 concentrations were measured in fasting blood samples. In the German and Italian cohort, the diagnosis of NAFLD and grading of NAFLD was assessed by ultrasound. Results: NAFLD was diagnosed in n = 50 patients of the German cohort (29.6%) and in n = 29 patients (72.5%) of the Italian cohort. In all three cohorts, miR‐122 was positively correlated with ALT and AST as well as with CK18 concentrations. MiR‐122 levels were higher in children with NAFLD compared with healthy controls. Conclusions: MiR‐122 levels in pre‐pubertal obese children could be a potential biomarker for paediatric NAFLD.